Strategi Pemasaran Nanas (Ananas Comosus) di Desa Wonua Morini Kecamatan Sabulakoa Kabupaten Konawe Selatan - Yudiastini, Kadek; Abdi, Abdi; Gafaruddin, Abdul (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2019)
This research is motivated by an increase in pineapple production in South Konawe Regency, in 2015 pineapple production reached 2,543 tons, in 2016 pineapple production reached 4,573 tons and in 2017 pineapple production reached 7,126 tons (BPS Southeast Sulawesi 2017). Increasing the production of pineapple requires a good marketing strategy so that pineapple can sell quickly. The research objective was to find out the strengths, weaknesses, opportunities, and threats of pineapple marketing and find out the marketing strategy of pineapple in Wonua Morini Village, Sabulakoa District, South Konawe Regency. Determination of the location of the study was carried out intentionally (purposive) with the consideration that Wonua Morini Village is one of the villages that has quite a lot of pineapple production compared to other villages. The number of respondents of pineapple farmers is 33 farmers. Data analysis using SWOT analysis using the IFE (Internal Factors Evaluation) matrix, EFE Matrix (External Factors Evaluation), and IE (Internal External) Matrix. The results of the study show that the right strategy for marketing pineapple is a growth strategy for concentration diversification.